UNVEILING THE HIDDEN GEM: THE ROLE OF SUSTAINABLE DESTINATION IMAGE AND LOCAL CO-CREATION IN FOSTERING POSITIVE WORD-OF-MOUTH AT LAKE TOBA GEOPARK - Dimas Nugraha; Novia Yuliarni; Bayu Setia (Faculty of Economic and Business, University of Pasundan, 2026)
This study aims to analyze the influence of Sustainable Destination Image and Experience Co-Creation on Positive Word-of-Mouth, with Memorable Tourism Experience as a mediating variable among tourists visiting Sibandang Island, part of the Toba Caldera UNESCO Global Geopark. The research employs a quantitative approach with a cross-sectional survey design. Data were collected from 220 tourists who have visited Sibandang Island using a purposive sampling technique and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Sustainable Destination Image and Experience Co-Creation have a positive and significant effect on both Memorable Tourism Experience and Positive Word-of-Mouth. Furthermore, Memorable Tourism Experience positively influences Positive Word-of-Mouth and partially mediates the relationships among the variables. These findings highlight the importance of a destination’s sustainability image and participatory experiences in creating memorable tourism experiences and encouraging positive tourist recommendations.